Generalized subcutaneous emphysema (pnenmoderma) in a dog - İlker Çamkerten; Arif Kurtdede; Abuzer Acar (Eurasian Journal of Veterinary Sciences)
This case was observed in a 3 year-old, male German Shepherd dog. In the anamnesis, ihe dog, being as a guard dog, was involved in a dog fighting wilh the owned dogs about two weeks ago, and had biting wounds on ils neck, back, and legs. There were emphysematous swellings on these regions one week later. Eventually, these swellings spread all over the body 15 days later. Parenteral enrofloxacin was administered to the dog for 3 weeks and local medication was applied lo the wounds. In clinical examination, there were fluctuant, crackle, and cold subcutaneous swellings all over the body, and deep wound traces on Ihe head and neck skin. Diagnosis was based on anamnesis and clinic findings. Wounds were opened operalively, cleaned by an iodide antiseptic, applied by hydrogen peroxide. Penicillin-streptomycin was administered intramuscularly for 5 days. The swellings disappeared one week after tho treatment. There was no reoccurrence wilhin one year. This case was thought to be of valuable to publish since it is seen rarely in dogs.